2001
DOI: 10.1177/026988110101500405
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacovigilance of olanzapine: results of a post-marketing surveillance study on 8858 patients in England

Abstract: Olanzapine is an 'atypical' antipsychotic indicated for the treatment of schizophrenia. We analysed adverse events (AEs) reported in primary practice in England. Dispensed prescriptions issued between December 1996 and May 1998 provided exposure data. Questionnaires sent to general practitioners provided outcomes. Frequently reported AEs were: drowsiness/sedation (n = 19), extrapyramidal disorder (n = 13) and unspecified side-effects (n = 33). Events with highest incidence density in first month and reason for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 7 publications
1
36
0
Order By: Relevance
“…Recent evidence has shown an association between olanzapine and diabetes 714. Most of the articles were case reports documenting the incidence of diabetes or hyperglycaemia with olanzapine.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence has shown an association between olanzapine and diabetes 714. Most of the articles were case reports documenting the incidence of diabetes or hyperglycaemia with olanzapine.…”
Section: Introductionmentioning
confidence: 99%
“…hyperprolactinaemia 24 ), or the safety and tolerability profiles for particular classes (e.g. long-acting injections 25 ) or brands 26 of drug. However, there is currently a lack of comprehensive information about the methods employed for assessing adverse antipsychotic effects across the broader evidence base (including, but not limited to, clinical trials), the types of effects being reported, and whether screening procedures differ according to the effects being assessed.…”
Section: Assessing and Reporting The Adverse Effects Of Antipsychoticmentioning
confidence: 99%
“…Two other studies which included clozapine found no increased DM risk (Lund et al, 2001 andWang et al, 2001), while Sernyak et al (2002) and Gianfrancesco et al (2002) both suggested that patients on clozapine had a greater risk of developing DM than those on conventional antipsychotics or non-users of antipsychotics. The report by Biswasl et al (2001) found only eight cases of diabetes among 8858 patients onolanzapine between 1996 and 1998 reported by responding clinicians to a pharmacovigilance questionnaire. Among the clinical studies, five found that the use of olanzapine was associated with a significantly greater risk of increasing blood glucose or insulin levels compared to those on risperidone or a control group (Melkersson and Hulting, 2001;Newcomer et al, 2002;Wirshing et al, 2002;Lindenmayer et al, 2003).…”
Section: Psychiatric Medications Predisposing To Dmmentioning
confidence: 99%